The Macedonian Language in Regard to Covid-19 - Violeta Janusheva (Thesis, 2020)
The new disease that appears in December 2019 affects all spheres of people’s everyday living and functioning. Bearing in mind that language reflects social phenomena and that lexicon is the most flexible language segment, new words and phrases inevitably enter the lexicon on a daily basis. These novelties generate new problems not only in the lexicon but in other language segments as well. Thus, this paper addresses the new words which emerge from the disease presence as well as the problems caused by their occurrence and use, in regard to the Macedonian orthography, morphology, syntax and lexicology. This is a qualitative research that has a descriptive design, and the corpus consists of numerous articles issued in electronic newspapers. Analysis and synthesis are the methods used for processing the data and reaching conclusions. The research results indicate that the Macedonian language lexicon undoubtedly is enriched with new words. However, this extension in the lexicon has plenty of orthographic, morphological and syntactic implications related to the Macedonian language norm.